THE ROLE OF SOCIAL CLASS IN SHAPING CITIZENSHIP: AN ANALYSIS OF THOMAS MARSHALL'S WORKS - Nuriyani, Riska; Arpannudin, Iqbal; Murdiono, Mukhamad; Ramadhan, Abhi Rachma (International Journal of Social Service and Research, 2025)
In the era of 21st-century disruption, fostering national character to strengthen identity and nationalism is crucial for forming inclusive citizenship. This research aims to deepen and broaden the understanding of how social class affects individuals' access to citizenship rights. This study employs a qualitative approach using the library research method, which involves compiling various references from previous studies relevant to the research subject to draw conclusions. The collected data are processed, analyzed, and presented descriptively and qualitatively in a logical and systematic manner, yielding inductive conclusions that begin with specific observations and lead to general conclusions. Inequality in access to education, disparities in employment opportunities, and limited political participation are challenges that need to be addressed to achieve inclusive and equitable citizenship. The challenges in Indonesia's education system encompass three main aspects: unequal access to educational, varying quality of education, and inconsistent allocation of budgets along with a lack of commitment from local governments to improve educational standards. These inequalities present significant challenges in realizing a fair and equitable citizenry system. This work is an essential reference for sociological, political science, and legal studies in discussing the dynamics of citizenship and social equality.